2021
DOI: 10.1364/oe.416245
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-light planar meta-absorber with wideband and full-polarization properties

Abstract: Absorbers have high potential application values in the military field, such as electronic screening, radar cross-section reduction and invisible cloaking. However, most methods have the defects of narrow bandwidth, low absorptivity, complex three-dimensional structure and fixed polarizations. In this paper, we realize an ultra-broadband and full-polarization planar metamaterial absorber (PMA) with a three-layer composite structure, which exhibits multi-resonant and impedance matching properties by combining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…As the incident angle increases, the absorption peak shifts towards higher frequencies. The reasons for this phenomenon are attributes to the fact that the equivalent impedance of TE and TM mode varies with the incident angles, which can be explained by the following equation [34]:…”
Section: The Performance Of Polarization Insensitive and Wide Inciden...mentioning
confidence: 99%
“…As the incident angle increases, the absorption peak shifts towards higher frequencies. The reasons for this phenomenon are attributes to the fact that the equivalent impedance of TE and TM mode varies with the incident angles, which can be explained by the following equation [34]:…”
Section: The Performance Of Polarization Insensitive and Wide Inciden...mentioning
confidence: 99%
“…[11] Shui et al reported a flexible and thin Ti 3 C 2 T X sponge composite absorber working at 0.3 THz-1.65 THz with absorption over 90% and with a thickness of about 2 mm. [12] The above literature suggested that both materials and structures can be explored to improve the absorption performance, [13][14][15][16][17][18] and thus the absorption bandwidth can be expanded with relatively minimal thickness.…”
Section: Introductionmentioning
confidence: 99%
“…One area where this technology shows particular promise is the development of tunable, multiband, and broadband metamaterial-based absorbers for use in the infrared (IR) wavelength range. These absorbers are essential for applications in spectroscopy, thermal emission, cloaking, and sensor technologies. Various designs have been proposed to achieve multiband absorption, including the vertical stacking of subwavelength metal structures, combining resonators of different sizes or shapes, and using grating-based Fabry–Perot (FP) structures …”
Section: Introductionmentioning
confidence: 99%